ANALISIS PROGAM KELOMPOK USAHA TERNAK“MAWAR” DALAM PENGEMBANGAN INOVASI PRODUK DI KELURAHAN PANGKALAN BALAI - Sulistijanto, Andi Budi; Marlina, Marlina (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2019)
Analysis of the "Mawar" livestock business group program in improving the welfare of the community in Pangkalan Balai, From the results of the research conducted, it shows that (1) the "Mawar" livestock business group program in improving the welfare of the community in Pangkalan Balai has not been maximized where there is a lack of knowledge in tackling diseases and good management of cages and animal feed. (2) The forms of policies determined by the government are the provision of loan capital with small interest, capital, facilities and infrastructure, and marketing of products produced by small industries. (3) With the existence of the "Rose" livestock business group in improving the welfare of the community in Pangkalan Balai Village at this time.